Are Gender and Generational Differences in Ethical Perceptions Real? An Empirical Study on Workplace in Turkey - YILDIZ ŞEN, MÜGE LEYLA (ISTANBUL UNIV, SCH BUSINESS, 2019)
Managing ethical perceptions is a complicated and important problem because unethical behavior can cause many negative outcomes for business organizations. The purpose of the study is to determine the gender and generational differences in ethical perceptions in the workplace. The sample of the study is 828 workers (460 of Gen Y, 256 of Gen X and 112 of baby boomers) In Turkey. The findings suggest that women are more ethical than men. There is also evidence to suggest that generational differences are an important factor in understanding the differences of ethical perceptions of workers in the workplace. Moreover, Generation Y in Turkey tend to be more tolerant of unethical behavior than Generation X in the workplace. The results, limitations, and implications of the research is presented for managers.
Keywords: Ethical perception; Generational differences; Gender; Millennial; Generation Y; Generation X; Baby Boomers; DECISION-MAKING; SPECIAL EMPHASIS; BUSINESS ETHICS; WORK VALUES; BEHAVIOR; PROFESSIONALS; EXPECTATIONS; LEADERSHIP; FACT